Vol 2 no 2 Tahun 2024 ANALISIS IMPLEMENTASI PERATURAN MENTERI PERDAGANGAN RI NO.40/M-DAG/PER/6/2022 TAHUN 2022 TENTANG LARANGAN IMPOR PAKAIAN BEKAS : DALAM SUDUT PANDANG BISNIS SYARI’AH. - nidhom, Misbahun (PRODI ES SEKOLAH TINGGI ISLAM KENDAL, 2024)
The activity of buying and selling imported used clothing is a problem that has not been solved, making researchers interested in conducting research on the Analysis of the Implementation of Regulation of the Minister of Trade of the Republic of Indonesia No.40/M-Dag/Per/6/2022 of 2022 concerning the Prohibition of Importing Used Clothes from a Sharia Business Perspective 'Ah. Implementation of the Regulation of the Minister of Trade of the Republic of Indonesia regarding the prohibition on the import of used clothing, where violations are still found. These violations were committed by distributors and traders because they ignored the Minister of Trade Regulation. If viewed from Islamic law, the buying and selling transactions carried out are considered not in accordance with Islamic law. The aim of this research is to find out how the Indonesian Minister of Trade Regulation is implemented regarding the prohibition on the import of second-hand clothing and in terms of Islamic law regarding the buying and selling of imported second-hand clothing.